Targeting Metabolic Syndrome in Psoriasis: A Review of Current Evidence and Non-Pharmacological Treatment Approaches - Dudek, Stanisław; Bętkowska, Aleksandra; Koziak, Weronika; Kornacka, Agata; Szostak, Kamila; Dudek, Wojciech; Byra, Anna; Tomaka, Rafał; Makieła, Michalina (Quality in Sport, 2025)
Introduction: Psoriasis is a chronic inflammatory dermatosis affecting approximately 1.5-5% of the population in developed countries. Besides visible cutaneous manifestations, psoriasis is linked to an increased prevalence of various systemic complications. The term metabolic syndrome refers to a cluster of cardiovascular risk factors, including hypertension, dyslipidemia, obesity, and hyperglycemia, which affect up to 25% of the general population. Aim of Study: This review examines current and emerging treatments for metabolic syndrome in psoriasis, emphasizing shared pathophysiology, non-pharmacological strategies, and the significance of interdisciplinary care and a holistic approach. Brief Description of the State of Knowledge: Psoriasis is closely associated with metabolic syndrome, which impacts about one-third of psoriasis patients and exacerbates symptoms through chronic low-grade inflammation and an altered adipokine profile. Lifestyle modification remains the primary therapeutic approach. Emerging treatments, including nutraceuticals like curcumin and cinnamon, show promise in managing metabolic syndrome and potentially improving psoriasis outcomes, though further research is needed. Conclusions: Diligent screening for metabolic abnormalities, early recognition, and interdisciplinary management, including lifestyle changes, are crucial for addressing cardiometabolic comorbidities and ensuring comprehensive care in patients with psoriasis.